LEARNING STRATEGIES FOR IMPROVING SPIRITUAL INTELLIGENCE AND THE QUALITY OF STUDENT CHARACTER EDUCATION AT NU KAPLONGAN ELEMENTARY SCHOOL - Suadnan, Suadnan (Media Inovasi Pendidikan dan Publikasi, 2025)
Elementary school (SD) is the first step or the main educational base for children, this is where children will easily form their character. Lack of spiritual intelligence in children or students will result in a person's character not being good. These symptoms are more pronounced in children and adolescents. In dealing with complex challenges in educating children's morals and behavior, especially in this very modern era, developments marked by the rapid flow of social media, or the information available will have an influence on the attitude or lifestyle of students. The formulation of the problems in this study are 1) What are the strategies to improve the spiritual intelligence of students at SD NU Kaplongan 2) What are the methods for enhancing the quality of character of students at SD NU Kaplongan. 3) What are the inhibiting and supporting factors in improving the character of students at SD NU Kaplongan. This study uses a type of qualitative research with a case study approach. The object of this research was carried out at SD NU Kaplongan. Data collection techniques use observation, interviews and documentation. Sources of data in this study include school principals, homeroom teachers, subject teachers, student guardians. The analytical techniques used in this study are data reduction, data presentation, drawing conclusions. The triangulation used to test the validity of the data is technique and source triangulation. The results of the study show that: (1) there are three reasons why spiritual intelligence and character education are carried out at SD NU Kaplongan, namely first, the learning content at SD NU Kaplongan is related to strengthening character education, second, there is a link between school programs in character education, and third to assist students in developing Islamic character, who have good morals and are autonomous. (2) A number of factors affect how Islamic character education is implemented at SD NU Kaplongan. The school environment comes first, followed by the family environment. Character education in the classroom is effective if it has the backing of the student's parents by getting used to it and providing examples related to habituation carried out at school. Conversely, if the student's collaboration and assistance are lacking, guardian then the character building will be difficult to realize. (3) The strategy for implementing spiritual intelligence and character education for students at SD NU Kaplongan is conducted using the phases of planning, carrying out, and assessing through routine, organized activities, and model behavior.